2014
DOI: 10.5665/sleep.3678
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Fragmentation in Mice Induces Nicotinamide Adenine Dinucleotide Phosphate Oxidase 2-Dependent Mobilization, Proliferation, and Differentiation of Adipocyte Progenitors in Visceral White Adipose Tissue

Abstract: Chronic sleep fragmentation (SF) induces obesity in mice and increased proliferation and differentiation of adipocyte progenitors (AP) in visceral white adipose tissue (VWAT) that are mediated by increased Nox2 activity. In addition, enhanced migration of bone marrow mesenchymal stem cells from the systemic circulation into VWAT, along with AP differentiation, proliferation, and adipocyte formation occur in SF-exposed wild-type but not in oxidase 2 (Nox2) null mice. Thus, Nox2 may provide a therapeutic target … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 62 publications
0
26
0
Order By: Relevance
“…Thus, it is possible that use of Resv as a dietary supplement in sleep disorder patients manifesting metabolic dysfunction may improve the latter via its antioxidant properties (28), since increased oxidative stress is clearly elicited by SF and promotes insulin resistance (2,3). However, the beneficial impact of Resv on the inflammatory phenotype of VWAT would suggest that the increased activation of inflammatory pathways elicited by SF (3) was reversed by Resv.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Thus, it is possible that use of Resv as a dietary supplement in sleep disorder patients manifesting metabolic dysfunction may improve the latter via its antioxidant properties (28), since increased oxidative stress is clearly elicited by SF and promotes insulin resistance (2,3). However, the beneficial impact of Resv on the inflammatory phenotype of VWAT would suggest that the increased activation of inflammatory pathways elicited by SF (3) was reversed by Resv.…”
Section: Discussionmentioning
confidence: 96%
“…SF also imposes adverse metabolic consequences such as increased appetite and food intake that ultimately promote the emergence of obesity (1,2).…”
Section: Introductionmentioning
confidence: 99%
“…Conceptualised as a chronic, low‐grade, inflammatory state, obesity is characterised by increased circulating inflammatory markers . Animal models confirm that poor sleep increases nicotinamide adenine dinucleotide phosphate activity in visceral white adipose tissue, producing adipose progenitors that lead to obesity and insulin resistance in sleep‐deprived mice …”
Section: Discussionmentioning
confidence: 99%
“…Thus, disrupted sleep such as occurs in OSAS markedly accelerates tumor progression and invasion even in the absence of intermittent hypoxia (IH; see below). More recent work from our laboratory has further indicated that in sharp contrast with other tissues, such as brain and adipose tissues (50–53), in which SF promotes increased NADPH oxidase activity, the opposite, i.e., reduced NADPH oxidase activity and expression occur within the solid tumor microenvironment, and underlie components of the increased aggressiveness of the tumor under SF conditions (54). These recent findings have prompted substantial interest and should lead to enhanced research efforts (55).…”
Section: Introductionmentioning
confidence: 99%